A Reformist Mongol Governor in China: Sayyid Ajall Shams al-Din Omar Bukhari (607-678 / 1211-1279) - Derya Coşkun (Journal of Universal History Studies, 2024)
Throughout history, there have been many politicians whose names are remembered and often recognized for their achievements in battles. We have come to know some of them closely due to their administrative initiatives. However, politicians who have made a name in every field are rare. One of these rare figures is Sayyid Ajall Shams al-Din Omar Bukhari, who gained fame for his reforms and the spread of Islam in China. Indeed, we are familiar with many politicians mainly for their war successes. However, those who have left their mark on the dusty pages of history in various fields are indeed rare. One such figure is Sayyid Ajall Shams al-Din Omar Bukhari, who made a name for himself with his reforms and the spread of Islam in China in the 12th century. This significant personality, who succeeded in bringing Islam to China in the mid-12th century, began to serve the Mongols after the capture of Bukhara by Genghis Khan in the year 616/1220. Due to his administrative abilities and knowledge of languages, Shams al-Din Omar attracted the attention of the Mongol Khans and was appointed as the governor of Yunnan. The reforms he implemented there quickly gained the love and acceptance of the people. The sympathy he gained facilitated the rapid spread of Islam in these lands. In this context, the article will focus on the identity, reforms, and contributions of Sayyid Ajall Shams al-Din Omar Bukhari, who is claimed to be from the lineage of the Prophet to the process of the spread of Islam in China.